2019
DOI: 10.3892/ol.2019.10018
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of patients with colorectal cancer without the recorded family history

Abstract: Colorectal cancer (CRC) is a multifactorial disease and one of the most malignant tumours. In addition to the sporadic form, familial occurrences, particularly hereditary non-polyposis CRC-Lynch syndrome (LS)-are often observed. LS is caused by a germline mutation in mismatch repair (MMR) genes, whose task it is to correct errors in the DNA structure that result from its replication. The aim of the present study was to stratify CRC patients using molecular diagnostics and next generation sequencing, according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
7
1
3
Order By: Relevance
“…We have performed a literature search in PubMed focused on population studies of CRC and LS in Slovakia from 2010–2020 using next-generation sequencing. In the Slovak population, only a few population studies of risk variants have been conducted to elucidate the etiology of CRC ( 55 57 ). In general, little is known about risk variants associated with CRC or LS in the Slovak population.…”
Section: Discussionmentioning
confidence: 99%
“…We have performed a literature search in PubMed focused on population studies of CRC and LS in Slovakia from 2010–2020 using next-generation sequencing. In the Slovak population, only a few population studies of risk variants have been conducted to elucidate the etiology of CRC ( 55 57 ). In general, little is known about risk variants associated with CRC or LS in the Slovak population.…”
Section: Discussionmentioning
confidence: 99%
“…We have performed a literature search in PubMed focused on population studies of CRC and LS in Slovakia from 2010-2020 using next-generation sequencing. In the Slovak population, only a few population studies of risk variants have been conducted to elucidate the etiology of CRC (Kašubová et al 2019;Mahmood et al 2014;Skerenova et al 2017). In general, little is known about risk variants associated with CRC or LS in the Slovak population.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological, molecular, genetic, and genomic studies have demonstrated that young women with BC show an increased rate of more aggressive subtypes with an overall worse prognosis, increased genetic susceptibility, differential tumor gene expression, specific genomic signatures, as well as alternations in epigenetic events including miRNA expression in comparison with postmenopausal women with BC [46]. Advances in novel technologies such as next-generation sequencing (NGS) and gene microarray have resulted in enormous progression and deluge sequence data about gene polymorphisms or determination of patterns of gene expression implicated in various pathological states [47,48,49,50]. Rummel et al [50] enrolled female patients within the Clinical Breast Cancer Project between 2001 and 2015 that were diagnosed with invasive BC before the age of 40.…”
Section: Pathological Characteristics and Tumor Behaviormentioning
confidence: 99%